ENT600 : McDonald's@Puncak Alam / Nur Khalidah Yahaya and Intan Syafiqah Mohamad Fauzi - Yahaya, Nur Khalidah; Mohamad Fauzi, Intan Syafiqah (2018)
This study focuses on fast-food industry, namely McDonald's. McDonald's@Puncak Alam is selected as a case study because it have high demand among UiTM student, Puncak Alam Community. McDonald's@Puncak Alam provides a variety of meal selection and promotion such as hamburgers and sandwiches, chicken and fish, snacks and sides, beverages, desserts and shakes, breakfast/AII-day breakfast and McCafe. In order to maintain customer loyalty, McDonald's@Puncak Alam must focus on the fact that there is an ever-changing market and that the wants and needs of consumers are constantly changing.